Pengaruh Pengawasan Internal dan Pemanfaatan Teknologi Informasi Terhadap Kepatuhan Pelaporan SPT Tahunan Pegawai Sekretariat Direktorat Jenderal Perhubungan Laut Kementerian Perhubungan Tahun 2024 - Nunki Atma Dewi; Guntur Ilhamsyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to determine and analyze the effect of internal supervision and the utilization of information technology on employees’ compliance in reporting Annual Tax Returns (SPT) within the Secretariat of the Directorate General of Sea Transportation, Ministry of Transportation. The research employs a quantitative approach using a survey method by collecting data through questionnaires, which were analyzed using multiple linear regression with the assistance of SPSS software. The research population consists of all employees of the Secretariat of the Directorate General of Sea Transportation, Ministry of Transportation, with the sample determined using a probability sampling technique. The results indicate that internal supervision and the utilization of information technology, both partially and simultaneously, have a significant effect on employees’ compliance in reporting Annual Tax Returns (SPT). These findings suggest that strengthening internal supervision and optimizing the use of information technology play an important role in improving Annual Tax Return reporting compliance.